Analysis of China’s Agri-food Imports In an Extended Gravity Model - Shakur S; Tang M; Ngo T (Massey University)
Since 2000, China has changed from a net exporter to a net importer of agri-food products to a point such that food security and agricultural trade balance are a major concern to Chinese authorities. This research estimated the effect of the ten explanatory variables that have impacted on China's accelerated food imports from 19 trading partners over 2000-2014. An extended gravity model that include economic, demographic, geographic factors and China's free trade agreements (FTAs) to 5 commodity groups separately, in addition to an aggregated data to allow a deeper understanding about the topic. Results from the research suggest that they all have varying but significant impacts on China’s agri-food imports. Agri-food imports to China are predicted to increase. For Chinese authorities to concentrate on own agricultural development and cost-effective trade with other
Keywords: China, Agri-food trade, Gravity model